Responsible consumption and production: influence of Sejahtera consumerism in post pandemic Covid 19 - Zainudin, Dolhadi (Sejahtera Consumerism Department of Business Administration Kulliyyah of Economics and Management Sciences IIUM, 2021)
Sustainable Development Goal (SDG) 12 is to achieve prosperity, peace, and unity in the world through responsible consumption and production. In the context of Falsafah Pendidikan Kebangsaan (PFK) or National Education Philosophy Malaysia, a peaceful, unity and prosperous world is known as sejahtera world. Sejahtera has a strong influence in Malaysia, particularly, consumerism in Malaysia. Responsible consumption and production with sejahtera will go beyond prosperity, peace and unity. Sejahtera consumerism and production in post covid-19 requires awareness, education, and reinforcement. Every consumer and producer should be naturally sejahtera consumers as well producers to practice responsible and sustainable consumerism. The lack of awareness about consumerism has been accelerating with industrial oriented education. Indeed, the reality of life encourages material possession. Ethical values have been forgotten in a trade-off of advancement in materialistic achievement. The old era of consumerism has been very challenging with social and economic instability. The covid-19 era posed more challenges due to new norms and restriction measures to curb covid-19. The community has no choice but to help among them through various social efforts and finance. In the meantime, the old norms of corruption and struggle for power have been dominated regardless of covid-19 situation. Every part of the society needs to participate actively in the consumerism movement. The feedback from students manifests the need to provide education, training and practice of consumerism.